PELUANG USAHA INDUSTRI ANIMASI DI INDONESIA - Nayaka, Tanaya; Dananjaya, Ida Bagus Putu (Pusat Penerbitan LPPM ISI Bali, 2024)
The animation industry in Indonesia has shown significant growth in recent years, fuelled by the increasing demand for creative content across various media platforms, such as film, television, social media, and gaming. This research aims to identify business opportunities in Indonesia's animation sector and analyze the factors influencing its growth. The research method used is a literature study and a survey of local animation industry players, including animation studios, independent animators, and educational institutions. The results show that technological support, increased access to digital platforms, and government programs that encourage creativity provide excellent opportunities for the growth of the animation industry in Indonesia. However, challenges such as lack of investment, limited skilled human resources, and lack of access to international markets must be overcome. The conclusion of this study emphasizes the importance of strengthening the animation industry ecosystem through collaboration between the education sector, government, and industry to create a business climate that supports sustainable growth.